Tuberculosis Incidence and Its Predictive Factors among Patients Receiving Antiretroviral Therapy in Dilla Hospital, Ethiopia - Sapa Wolde BEKALO; Yacong BO; Xiaoqin CAO; Chofore Almaz HAILE; Chunhua SONG; Kaijuan WANG; Ling WANG; Quanjun LU (Iranian Journal of Public Health, 2017)
Please provide alternate text for this image to ensure accessibility for users with text-only browsers or assistive devices